Using Fire to Increase the Scale, Benefits, and Future Maintenance of Fuels Treatments - North, Malcolm; Collins, Brandon M; Stephens, Scott (Journal of forestry, 2012)
The USDA Forest Service is implementing a new planning rule and starting to revise forest plans for many of the 155 National Forests. In forests that historically had frequent fire regimes, the scale of current fuels reduction treatments has often been too limited to affect fire severity and the Forest Service has predominantly focused on suppression. In addition to continued treatment of the wildland urban interface, increasing the scale of low- and moderate-severity fire would have substantial ecological and economics benefits if implemented soon. We suggest National Forests identify large contiguous areas to concentrate their fuels reduction efforts, and then turn treated firesheds over to prescribed and managed wildfire for future maintenance. A new round of forest planning provides an opportunity to identify and overcome some of the current cultural, regulatory, and institutional barriers to increased fire use that we discuss.